YGK Payroll System - Lee Ling, Ling (2012)
The main purpose of this project is to provide admin of YGK Jewellery Sdn. Bhd. the easiest way to calculate the target commission, count the total salary and produce a detail salary slip and produce a total monthly commission report and whole year total report in details. This project is carried out to solve the problem face by the admin of YGK Jewellery Sdn. Bhd. such as waste a lot of time in calculate the commission and target commission of each employee since the rate of commission and target commission of supervisor and sales assistants are different. With this project, the admin can count the total salary of each employee easily and also can produce the salary slip and a whole year total report in details. With this, it will save a lot of time and also easy the work of admin in payroll calculation activity.